Impact of fatigue in Rheumatic Diseases in the work environment: A qualitative study - Connolly, Deirdre; Doran, Michele (My University, 2015)
Fatigue is a symptom of arthritis that causes difficulty at work. An improved understanding of this symptom could assist it s management in the work environment. The aim of this study was to explore people with rheumatic diseases’ experiences of fatigue in work. A qualitative descriptive design was us ed with semi-structured interviews and a constant comparative method of data analysis. There were 18 participants, the majority of them female with Rheumatoid Arthritis (RA) and working full-time. Three themes were identified: “Impact of fatigue on work pe rformance” with cognition, mood and physical abilities being the main difficulties reported. In the second theme “Disclosure at Work” participants discusse d disclosing their disease to empl oyers but reported a lack of understanding of fatigue fr om colleagues. The final theme “work-based fatigue management strategies” included cognitive stra tegies and energy management techniques, which were mainly self-taught. In this study, fatigue was reported to impact on many areas of work performance with limited unde rstanding from colleagues and employers. Interventions from health professionals to assist with development of work-related self-management skills are required to assist wi th symptom management in the work place. Such interventions should include education to employers and colleagues on the nature of fatigue in Rheumatic diseases.
PUBLISHED
Keywords: fatigue; rheumatic diseases; disclosure; workplace accommodations; education; Inclusive Society; FATIGUE; Rheumatic Diseases; WORK PERFORMANCE